Gekko phuyenensis sp. nov. (Squamata: Gekkonidae), a new species from southern Vietnam - Nguyen, Vu Dang Hoang; Nguyen, Luan Thanh; Orlov, Nikolai L.; Murphy, Robert W.; Nguyen, Sang Ngoc (Zootaxa, 2021)
A new species of the genus Gekko Laurenti, 1768 is described from Phu Yen Province, southern Vietnam based on morphological and molecular evidence. Gekko phuyenensis sp. nov. differs from other congeners by its moderate size, with a snout-vent length of 90.2–92.8 mm; nares in contact with rostral; internasal 1; interorbitals 35 or 36; ventrals 30–32; dorsal tubercle rows 9 or 10; precloacal pores 12 or 13 in males and precloacal pits 13 in female; subdigital lamellae under first finger 18–21, fourth finger 19 or 20, first toe 18–20, and fourth toe 21–23; subcaudals median enlarged; no webbing between toes; and the absence of tubercles on hind limbs. Molecular phylogenetic analyses of mitochondrial gene COI (681 bp) using the geckos from Phu Yen and its congeners in southern Vietnam resolve the new species as the sister lineage to G. cf. grossmanni from Khanh Hoa Province. Genetic distances between G. phuyenensis sp. nov. and its congeners in southern Vietnam range from 16.9–24.2%. The discovery of this new species raises the number of known species of Gekko in Vietnam to 14.